Igualdade e diferenças: a aplicação do princípio da igualdade no julgamento de demandas que versem sobre desigualdades de gênero, raça e sexualidade - SILVA, Ítalo Viegas da (2023)
This dissertation focuses on the application of the equality principle by the Judiciary in legal disputes that deal with material and symbolic inequalities between social groups due to gender, race and sexuality discrimination in Brazil. The theme developed here stems from the research problem that questions which meanings can compose the equality principle, so that a common status can be attributed between social groups that are unequal both materially and symbolically, without this implying the disregard of the differences of those who have claimed legal valuation. As initial hypotheses, it was considered counter-hegemonic theories that demonstrate an insufficiency of the classic categories of the equality principle to solve controversies of a plural and asymmetric reality, and also that the equality principle must mutually incorporate parameters of redistributive justice and recognition that consider the discriminatory processes that produce gender, race and sexuality inequalities. To address these parameters, the main theoretical framework of this study is Nancy Fraser’s “Redistribution or Recognition? A Political-Philosophical Exchange”, which was chosen after a dialogue between her, Charles Taylor and Axel Honneth. Added to this perspective, the research also combined counter-hegemonic epistemologies – Critical Theory of Race, Intersectional Feminism and Queer Theory – to dialogue with the theoretical framework and with the traditional notions of the equality principle. That said, the general objective of the dissertation is to propose meanings to the equality principle that have the power to attribute a common status among social groups, so that this doesn’t cause a disregard of differences, such as those structured by markers of gender, race and sexuality, which have been claiming their legal valuation. In order to fulfill this mission, the following specific objectives were chosen: a) analyze the thinking of Charles Taylor, Axel Honneth and Nancy Fraser about the categories of recognition and redistribution; b) verify the classic meanings of the equality principle in Brazilian constitutionalism, as well as confront them with the counter-hegemonic epistemologies produced by vulnerable social groups; c) evaluate representative actions, such as the Action for Non-compliance with Fundamental Precepts nº 186/DF (which deals with the reservation of openings in higher education based on ethnic-racial criteria), the Direct Action of Unconstitutionality nº 5617/DF (which discusses the reserve of the financial quota of the electoral fund in favor of women candidacies) and the Direct Action of Unconstitutionality nº 5543/DF (which debate the prohibition of blood donation due to sexual orientation), in order to understand the recognized and incipient meanings of the equality principle held by the Federal Supreme Court. This research has a highly qualitative nature, with a legal-social aspect of legal investigation, based on inductive reasoning and combined with the content analysis technique. At the end of the study, in addition to confirming the hypotheses, it was found that the meanings of the equality principle are still in an embryonic stage within the Judiciary, which is why it is necessary to mature the debate. Furthermore, two major dimensions were identified within this principle, the formal and the material, the latter with recent addition of meanings, such as equality as a prohibition against discriminatory treatment. Finally, a dogmatic proposal was presented regarding the application of the equality principle in Brazilian lawsuits that address material and symbolic inequalities between social groups due to gender, race and sexuality discrimination.